Caracterização molecular e bioquímica da adaptação de uma variedade comercial de tomate (Solanum lycopersicum L.) ao sistema de produção da agricultura natural - Tavares, Nelson Salgado (2017)
This study addressed the adaptation and production of tomato plants grown with and without organic fertilizers in crops of the commercial variety “Especial para Salada”, whose seeds were produced by Topseed® (T0) and selected using the techniques of nature farming in 15 consecutive plantings (T15). Comparisons were made between T15 and T0 in the non-irrigated planting systems nature farming without fertilizer (NF) and organic agriculture with organic fertilizer (OF) and without the use of pesticides. Cultivation was carried out at West Virginia University Organic Agriculture Farm - WVUOAF (USA) divided into two treatments: nonfertilized (NF-T15, NF-T0); and two fertilized with organic compost (OF-T0 and OF-T15). In the experimental design of randomized blocks with five replicates and five plants per replicate, the production and the molecular characteristics of the plants were determined. For the biochemical studies, planting with the same treatments was performed in the municipality of Marechal Floriano, ES, Brazil. The non-fertilized plants NF-T15 and NF-T0 showed the best yields with the lowest losses of fruits damaged by diseases and pests. The NF-T15 tomato plants showed more efficient defenses despite having the lowest lignin contents (6%) in the fruits, and fewer flavonoids in the leaves. The fertilized tomato plants OF-T0 and OF-T15 had more lignin in the fruits and more flavonoids in the leaves, but they had the highest yield losses. The results of gene activity of T15 and T0 grown without nitrate showed that T0 tomatoes had the same levels of expression as the T15 plants in five of the six genes studied in the roots, which shows that T0 adapted to the absence of inorganic nitrogen. Regardless of the medium with or without nitrate, the NRT1 gene activities in the leaves were the highest in T0 and the lowest in T15. This result can be related to the susceptibility of the fertilized plants and the defenses of the non-fertilized plants. The NF-T15 tomatoes produced 29 t/ha, and the NF-T0 under the same conditions yielded 38 t/ha. The results showed that T0 achieved fast adaptation in this first crop without fertilizers and that T15 cultivated for many years without fertilizers showed more efficient resistance in the non-fertilized tomato plants. The organic fertilizer contributed to lower gene activity associated to the defense in the fertilized plants. For this reason, fertilization was harmful to the productivity of tomato plants grown in the organic planting system.